Mangiferin Mitigates Gastric Ulcer in Ischemia/ Reperfused Rats: Involvement of PPAR-γ, NF-κB and Nrf2/HO-1 Signaling Pathways - Mahmoud-Awny, Magdy; Attia, Ahmed S.; Abd-Ellah, Mohamed F.; El-Abhar, Hanan Salah (PLOS ONE, 2015)
Mangiferin (MF), a xanthonoid from Mangifera indica, has been proved to have antisecretory and antioxidant gastroprotective effects against different gastric ulcer models; however, its molecular mechanism has not been previously elucidated. Therefore, the aim of this study was to test its modulatory effect on several signaling pathways using the ischemia/reperfusion model for the first time. Animals were treated with MF, omeprazole (OMP), and the vehicle. The mechanistic studies revealed that MF mediated its gastroprotective effect partly via inducing the expression of Nrf2, HO-1 and PPAR-γ along with downregulating that of NF-κB. Surprisingly, the effect of MF, especially the high dose, exceeded that mediated by OMP except for Nrf2. The molecular results were reflected on the biomarkers measured, where the antioxidant effect of MF was manifested by increasing total antioxidant capacity and glutathione, besides normalizing malondialdehyde level. Additionally, MF decreased the I/R-induced nitric oxide elevation, an effect that was better than that of OMP. In the serum, MF, dose dependently, enhanced endothelial nitric oxide synthase, while reduced the inducible isoform. Regarding the anti-inflammatory effect of MF, it reduced serum level of IL-1β and sE-selectin, effects that were mirrored on the tissue level of myeloperoxidase, the neutrophil infiltration marker. In addition, MF possessed an antiapoptotic character evidenced by elevating Bcl-2 level and reducing that of caspase-3 in a dose related order. As a conclusion, the intimated gastroprotective mechanisms of MF are mediated, partially, by modulation of oxidative stress, inflammation and apoptosis possibly via the Nrf2/HO-1, PPAR-γ/NF-κB signaling pathways.